ANALISIS EFEKTIVITAS PENJUALAN BAHAN BAKAR MINYAK DALAM PENCAPAIAN TARGET ANGGARAN PENJUALAN PADA PT. PERTAMINA (PERSERO) MARKETING OPERATION REGION II - Ardhea Helmalia Alfitri; Jusmani Jusmani; Rismansyah Rismansyah (Journal of Management Small and Medium Enterprises (SMEs), 2023)
This study aims to determine the analysis of the effectiveness of fuel oil sales in achieving the sales budget target. The data collection techniques in this study are documentation and interviews. The data analysis techniques are descriptive qualitative analysis and quantitative analysis. The data used in this study are secondary and primary. Based on the results of the study, the effectiveness of Pertalite fuel oil sales in 2018, 2019, 2020, and 2021 is in the highly effective category and the effectiveness of Pertamax fuel sales in 2018 and 2019 is in the ineffective category but in 2020 and 2021 it is in the highly effective category. So it can be seen that sales effectiveness affects the success or failure of a company in achieving its targets and objectives. Keywords: Effectiveness; Target Achievement; Sales Budget; Fuel Oil